Bank Services in Banking Activities: A Literature Review - Mileni Rahayu; Restu Fauzi; Muhammad Resa Fadilah; Raflika Yogi Firmansyah; Dimas Herlangga (Samudra Publisher, 2024)
This research discusses the meaning, function and services of bank services in banking activities. Banks play an important role as financial institutions that collect funds from the public and channel them back in the form of credit, as well as providing various financial services that facilitate customer financial transactions and management. The main function of banks includes raising funds through products such as savings, time deposits, and current accounts, which are then used to provide credit to individuals, businesses, and governments. This function supports efficient resource allocation and economic growth. In addition, the bank provides payment, fund transfer and credit card services, as well as utilizing technology through internet banking and mobile banking to increase convenience and flexibility for customers. Technological developments and stringent regulations have changed the way banks operate, increasing the stability of the financial system and expanding access to financial services. Through the various services offered, banks not only meet customers' financial needs but also contribute to overall economic stability and progress. This article highlights the important role of banks in the modern economy and the positive impact of innovation in banking services on efficiency and economic growth. This research uses a literature study approach to examine various aspects of bank functions and services and their impact on the economy.